Mujeres migrantes y desigualdades socioterritoriales en barrios populares de San Carlos de Bariloche: tensiones y discursos contrapuestos - Matossian, Brenda (2016)
San Carlos de Bariloche city, in argentinian Patagonia, experienced a demographic and urban growth in which international and internal migration had a significant role. These migrants have built “new” neighborhoods through which the city has expanded, following a dispersed city model. This fast growth deepened a pattern of polarized and strong socioterritorial inequalities, which is distinctive of cities with neoliberal models development. In this context, the last fifteen years, popular sectors have experienced new partnership strategies developed largely by women with strong neighborhood leadership, many of them are also migrants. These new strategies were concreted through the most legitimate neighborhood institutions in the middle cities of argentinian Patagonia: Neighborhood Councils. In this paper, we study, on the one hand, the resistance processes at a neighborhood scale, headed by women, through a particular event that has been the controversial installation of a Walmart`s supermarket (called Changomas) which led to the implementation of a referendum. Moreover, we will analize the tensions and conflicting speeches - through in-depth interviews and main local newspapers analysis- that have contributed the formation of a hegemonic imaginary based on binary representations of the city: one designed for tourism (“the Swiss Argentina”) and the other for the popular sectors in the periphery (“El Alto”).